DEVELOPING MUTE VIDEO OF DESCRIPTIVE TEXT TO TEACH BEAUTY MAJOR STUDENTS’ READING COMPREHENSION - Saputra, Komang Ayu Lakmitasari; Asi, Natalina (Journal Compound: Improving the Quality of English Education, 2020)
This research was aimed to develop the mute video for teaching reading comprehension of descriptive text based on the vocational English syllabus and the students’ need. This Research and Development (R and D) was conducted to develop a mute video for the tenth grade students of beauty major. The subject of this research was the tenth grade students of beauty major at SMKN 3 Palangka Raya. The used instruments are questionnaire, expert validation, and observation which were distributed to the students, teacher and also the experts. The collected data were analyzed and described qualitatively. The result of data analysis showed that students required relevant media to their need and interest and the teacher needed to have a reference media in teaching reading comprehension of descriptive text to the beauty major. Considering to those result, the product of this research was the two mute videos of descriptive text which consisted of beauty content. The result of expert validation showed that the mute videos were valid to implement to the class, the mute videos need to improve on the grammar, visual cues, gap and color grading of the video. The data obtained from observation showed that the mute videos developed were helpful for the teacher to teach descriptive text in reading comprehension. The students were feeling helpful and excited to learn descriptive text using the mute video developed. The teacher also could make the mute video as one of the references media in teaching reading comprehension of descriptive text to the beauty major students at the tenth grade of Vocational High School.